Raising Bond Capital in Segmented Markets - Siani, Kerry Y (Review of Financial Studies, 2025)
The difference between corporate bond yields at issuance and in secondary markets, the “issuance premium,” spikes in bad times, raising firms’ capital costs. Using new bond-level data and high-frequency variation in bond supply and demand, I estimate a model of primary markets with imperfectly elastic investors, endogenous bond supply, and underwriter frictions that quantifies drivers of issuance premiums. I find underwriters’ favoritism toward investors increases issuance premiums’ levels and cyclical variation. On the other hand, relatively elastic investors allow primary markets to absorb large bond issuances. My findings inform policies targeted at bond issuance markets.